Analysis of Industry-Based Plantation Commodity Development in the Area of Jambi Province - Lukman, Lukman (Jurnal Samudra Ekonomi dan Bisnis, 2022)
The purpose of this study is to analyze the advantages of plantation commodities in Jambi Province. Shift-Share Analysis and Location Quotient Analysis were used to analyze data. The research results conclude several things. First, there are the comparative advantages of oil palm and rubber throughout Jambi. Second, rubber and palm oil in the commodity base sector in Kerinci, Merangin, Batang Hari, Bungo; coffee and cinnamon are the base sectors in Kerinci, Merangin, Sorolangun; and, chocolate in Bungo and Kerinci. Third, palm oil and rubber are dominant and their growth potential in all areas in Jambi; coffee, cinnamon, cocoa plantations are dominant and their growth potential are in Kerinci, Merangin, Bungo; and, clove, coconut, areca nut, candlenut, kapok, sugar palm, vanilla, sugar cane, patchouli are less developed. Finally, there are three clusters oriented towards ease of market access, proximity of raw materials and availability of labor.